Well Done! Effects of Positive Feedback on Perceived Self-Efficacy, Flow and Performance in a Mental Arithmetic Task - Peifer, Corinna; Schönfeld, Pia; Wolters, Gina; Aust, Fabienne; Margraf, Jürgen (Frontiers in Psychology, 2020)
Self-efficacy is a well-known psychological resource, being positively associated with increased performance. Furthermore, results from field studies suggest a positive impact of self-efficacy on flow experience, which has not yet been tested experimentally. In this study, we manipulated self-efficacy by means of positive feedback and investigated whether self-efficacy serves as a mediator in the relation of positive feedback and flow and in the relation of positive feedback and performance. Our sample consisted of 102 participants (63 female, 39 male). The experimental group received positive feedback after accomplishing five minutes of mental arithmetic tasks on a computer, whereas the control group received no feedback. After that, a second session of a mental arithmetic task was conducted for five minutes. Mediation analyses confirmed that specific self-efficacy mediated a positive effect of positive feedback on flow as well as on both performance measures (quality and quantity) in a subsequent task. However, direct effects of feedback on flow and on performance were not significant, which suggests the presence of other mechanisms that remain to be investigated.